CHARACTERIZATION OF HYDROXYAPATITE FROM CHANNA STRIATA AND SCOMBEROMORUS COMMERSON FISH BONE BY HEAT TREATMENT - Anggraini, Rista Mutia; Restianingsih, Tika; Deswardani, Frastica; Fendriani, Yoza; Ananda Putri Purba, Roedearni (JOURNAL ONLINE OF PHYSICS, 2023)
Hydroxyapatite (HAp) biomaterials have been successfully obtained from Channa striata and Scomberomorus commerso fish bone. Heat treatment was chosen as the method to get it. Heat treatment was done at 400oC, 600oC, and 800oC. The X-ray diffractometer (XRD) was used to determine the crystalline phase and crystallography properties. Based on XRD data and JCPDS 09-0432, all samples showed the phase of HAp. However, the Î²-TCP phase has been found in samples from Scomberomorus commerso, which calcined at 600oC and 800oC. The crystallite size of HAp from Channa striata fish bone increased as followed by higher temperature, and Scomberomorus commerso has the same crystallite size on samples that calcined at 600oC and 800oC. The microstrain of both samples has the same trend: the higher the temperature, the lower the microstrain. The temperature also affected the crystallinity sample; the higher the calcined temperature, the improved crystallinity. Fourier Transform Infrared (FTIR) data determined the functional groups of samples. The functional groups that appeared were OH-, PO43-, and CO32-. The mass of samples before calcined differs from after calcined, where the mass after calcined is smaller than before. The higher the temperature we used, the more decreased yield percentage we got.